Sorghum cutting and grazing for hay production - Santos, Leandra Cristina Soares; Moura, Marielly Maria Almeida; Mendes, Lívia Rodrigues; Rodrigues, Brenda Souza; Madureira, Mariana Rabelo; Santos, Keitty Fabiany Alves; Fonseca, Silvana Melissia Rabelo; Ribeiro, Joyce Costa; Fonseca, Layza Lorena Medeiros; dos Santos , Jaine Aparecida; Mendes , Anne Karoliny Fernandes; Fernandes, Álvaro Henrique Lopes; et al. (Seven Editora, 2024)
Sorghum hybrids (Sorghum bicolor cv. Bicolor) with Sudan grass (Sorghum bicolor cv. Sudanense) have been gaining increasing importance in feeding herds, due to their resistance to drought, great speed of establishment and growth, high capacity for tillering and regrowth after cutting or grazing (which allows successive uses), good nutritional value and great capacity for dry matter production. For the crossing of the species, a strain of Sudan grass (Sorghum sudanense (Piper) Stapf.) is used as a male and, as a female, a strain of grain sorghum (Sorghum bicolor (L.) Moench. Thus, the use of hay from sorghum for cutting and grazing is one of the alternatives to the problem of seasonality of forage plants, allowing the surplus produced, or in exclusive cultivation areas, to be stored and used in animal feed in times of scarcity. The objective of this work was to carry out a review of the narrative literature on sorghum, cutting and grazing for hay production. DOI:https://doi.org/10.56238/sevened2024.023-015